2016
DOI: 10.1088/0963-0252/25/6/065019
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of negative hydrogen ion production at low pressure by controlling the electron kinetics property with transverse magnetic field

Abstract: In a volume production H − ion source, independent control of electron energy distribution between the driver region and the extraction region is crucial for the efficient production of H − ions due to its unique volume production mechanism. However, at the low pressure regime compatible to ITER operation, it is difficult to control electron energy distribution separately because the nonlocal property dominates the electron kinetics. In this work, we suggest a new method to control the locality of electron kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…From another point of view, our results indicate that it is possible to control the eepf within the magnetically expanding plasma generated by the ECR or helicon sources by changing the bounce region of confined electrons according to the magnetic field conditions. It is meaningful that these characteristics can play a leading role in the generation of specific radical and ion species in the plasma processing, in which the spatial distribution of eepf is a decisive factor [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, our results indicate that it is possible to control the eepf within the magnetically expanding plasma generated by the ECR or helicon sources by changing the bounce region of confined electrons according to the magnetic field conditions. It is meaningful that these characteristics can play a leading role in the generation of specific radical and ion species in the plasma processing, in which the spatial distribution of eepf is a decisive factor [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…the frequency scale of the electron-electron collision greatly exceeds the inelastic collision between low energy electrons and neutral species. Recently, we observed that the magnetic filter field changes the bi-Maxwellian EEPF to the low-energy populated Maxwellian [39], which is similar to the effect of gas pressure on the EEPF. We are attempting to understand the mechanism of magnetic filter in the context of the enhanced electron-neutral collision by the electron confinement due to the filter field.…”
Section: Destruction Processmentioning
confidence: 56%
“…A systematic Boltzmann analysis is performed on the EEDF, to act as the support for the model of SiH 4 -containing plasmas. Due to the formant of vibrational excitation, the EEDF drops sharply in the energy range of 0.1-4 eV in low reduced electric field (E/N < 100 Td) [56]. The presence of the formant probably contributes to the electron energy loss in the vibrational excitation.…”
Section: Discussionmentioning
confidence: 99%